Measuring accessibility: Methods and issues - Eric J. Miller (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This paper discusses the current state of transport accessibility measurement. It demonstrates that all commonly used measures are special cases of a generic accessibility model that conforms to a few fundamental axioms. The paper also shows that accessibility measures are fundamentally tied to travel behaviour. These ties should be explicitly recognised and exploited to construct theoretically defensible and practically useful measures.
Keywords: 330